Ultrastructural and genetic characteristics of endolithic cyanobacterial biofilms colonizing Antarctic granite rocks - Ríos, Asunción de los; Grube, M.; Sancho, Leopoldo G.; Ascaso, Carmen (FEMS Microbiology Ecology, 2007)
9 pages, and figures, and tables statistics The precise identification of the cyanobacteria that comprise an endolithic biofilm is hindered by difficulties in culturing the organisms found in these biofilms and a lack of previous molecular and ultrastructural data. This study characterizes, both at the ultrastructural and molecular level, two different cyanobacterial biofilms found in fissures of granite from continental Antarctica. Electron microscopy revealed structural differences between the two biofilms. One was only loosely adhered to the substrate, while the other biofilm showed a closer association between cells and rock minerals and was tightly attached to the substrate. Cells from both biofilms where ultrastructurally distinct, displaying, for instance, clear differences in their sheaths. The amounts of EPS and their organization associated with the cyanobacteria may determine the differences in adhesion and effects on the lithic substrate observed in the biofilms. By sequencing part of the 16S rRNA gene, the two cyanobacteria were also genetically characterized. The gene sequence of the cells comprising the biofilm that was tightly attached to the lithic substrate showed most homology with that of an endolithic cyanobacterium from Switzerland (AY153458), and the cyanobacterial type loosely adhered to the rock, clustered with Acaryochloris marina, the only organism unequivocally known to contain chlorophyll d. This study reveals the presence of at least two different types of endolithic biofilm, dominated each by a single type of cyanobacterium, able to withstand the harsh conditions of the Antarctic climate. Peer reviewed